Penguatan Kapasitas BUMDes dan Prakarsa BUMDesma di Kecamatan Ambarawa Kabupaten Pringsewu - Fahmi, Teuku; Yulianto (Kreativasi : Journal of Community Empowerment, 2024)
The initiative to establish joint village-owned enterprises (BUMDesma), as local-scale village businesses run by BUMDes, has become increasingly common since the enactment of Law Number 6 of 2014 on Villages. Developing these joint BUMDes is also a strategic policy of the current "Kabinet Indonesia Maju". This community service activity focuses on increasing the capacity of village-owned enterprise managers in Ambarawa District. The activities conducted are in the form of training and mentoring to improve the institutional capacity of each BUMDes in Ambarawa District. The methods used in this activity include: the stage of increasing cognitive aspects, the stage of mentoring and empowerment, and the stage of advocacy. Specifically, this community service activity has led to several achievements, including: in terms of cognitive aspects, there has been an increase in understanding of the existence of BUMDes in improving the village economy to become larger and stronger. The community service activities conducted have successfully increased the knowledge and understanding of the participants by 12.50%. In practical terms, there has been an emergence of initiatives to develop joint BUMDes among BUMDes managers in Ambarawa District.